Modal identification of train passenger seats based on dynamic tests and output-only techniques - Silva, Patricia (2023)
Railways are one of the most efficient and widely used mass transportation systems for mid-range distances, also being pointed out as the best strategy to reach European Union decarbonisation goals. However, to increase railways attractiveness, it is necessary to improve the quality of the ride, namely its comfort, by decreasing the vibration at the passenger level. This article describes the experimental vibration modal identification of train seats based on a dedicated set of dynamic tests performed on Alfa Pendular and Intercity trains. This work uses two output-only modal identification techniques: the transmissibility functions and the Enhanced Frequency Domain Decomposition (EFDD) method. The last method allows us to clearly distinguish the seat structural movements, particularly the ones related to torsion and bending of the seat frame, from the local vertical foam vibrations. The natural frequencies and mode shapes are validated by matching the results derived from the transmissibility functions and EFDD method. The identified modal parameters are particularly relevant to characterise the vibration transmissibility provided by the foams (local transmissibility) and the vibration transmissibility derived from the metallic seat frame (global transmissibility).